2016
DOI: 10.5620/eht.e2016013
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of a humidifier disinfectant case from a toxicological perspective

Abstract: An analysis of patients and fatalities due to exposure to polyhexamethylene guanidine (PHMG) shows that PHMG causes mainly lung diseases such as pulmonary fibrosis. However, no research on the other organs has been conducted on this matter yet. So, an in-depth discussion on toxicological techniques is needed to determine whether or not PHMG is toxic to organs other than just the lungs. For the test of target organ toxicity by PHMG exposure, a toxicokinetic study must first be conducted. However, measurement me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…24 However, it is suggested that polyhexamethylene guanidine may be associated to toxic effects, including pulmonary fibrosis, when used in humidifier disinfectants. 23 Thus, the results of this study should be used with caution and more cytotoxic tests should be performed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…24 However, it is suggested that polyhexamethylene guanidine may be associated to toxic effects, including pulmonary fibrosis, when used in humidifier disinfectants. 23 Thus, the results of this study should be used with caution and more cytotoxic tests should be performed.…”
Section: Discussionmentioning
confidence: 95%
“…Polyhexamethylene guanidine may have toxic effects, such as causing pulmonary fibrosis, when used in humidifier disinfectants. 23 Other studies showed that PHMGH presented lower…”
Section: Methodology Formulation Of Experimental Resin Sealantsmentioning
confidence: 95%
“…This result may have a positive impact when the cytotoxicity concern is addressed. Despite the high antibacterial activity, when previously used in humidifier disinfectants, it was suggested that molecules of polyhexamethylene guanidine led to toxicological effects 31 . In this way, the possibility of use PHMGH for a short time of contact with the material may bring advantages, decreasing possible PHMGH remnants on polymer structure and cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…60 An analysis of patients and fatalities attributed to inhalation exposure to PHMG indicates that this chemical mainly causes lung diseases, such as pulmonary fibrosis. 61 Of the known main components of the humidifier disinfectants, PHMG has been identified as the chemical substance that caused the most deaths. In surveys conducted to identify victims of the humidifier disinfectant, 22% of the research participants answered that they had used the humidifier disinfectant, and 21% complained of side effects.…”
Section: Smentioning
confidence: 99%